A poetic playground: collaborative practices in the Peak District. (18th August 2017) - Cooper, David
Abstract: The literary map of the Peak District is surprisingly thin. This article explores how this lacuna has been addressed by a range of contemporary writers who have made the Peak District a site of poetic hyperactivity: a landscape of creative processes and practices; projects and poems of place. Paying particular attention to texts by Helen Mort, Mark Goodwin and Alec Finlay, the article contends that much contemporary Peak District poetry is underpinned by imaginative and formal experimentation: a shared commitment to the exploration of new ways of perceiving, practising and representing landscape which is characterised by a collective playfulness. Moreover, the article argues that much contemporary Peak District poetry is shaped by collaboration as the poets placed under critical scrutiny share a preoccupation with finding new creative methodologies to articulate the communal experience of being-in-landscape.